Peningkatan Kemampuan Membaca Pemahaman Melalui Teks Bacaan Berbasis Metode Maternal Reflektif pada Siswa dengan Hambatan Pendengaran : Improving Reading Comprehension Skills in Students with Hearing Impairments Using Reading Texts Based on the Maternal Reflective Method - Fatmawati Ramadhani; Hermanto Hermanto (ITScience (Information Technology and Science), 2026)
This study aimed to assess the reading comprehension skills of a student with a hearing impairment before implementing reading texts based on the Maternal Reflective Method (MRM), to describe the implementation process, and to analyze improvements in reading comprehension skills following the intervention. The study employed a Single Subject Research (SSR) approach with an A–B–A design, comprising an initial baseline phase (A1), an intervention phase (B), and a second baseline phase (A2). The research subject was a fifth-grade student with a hearing impairment at SD Negeri 007 Sangkulirang. The study was conducted over eight sessions, consisting of two initial baseline sessions, four intervention sessions, and two second baseline sessions. Data were collected through reading comprehension tests, observation, and documentation, and subsequently analyzed using visual analysis based on changes in level, trend direction, data stability, and the percentage of overlap across phases. The results indicated that reading comprehension skills improved from 40% and 50% in phase A1 to 60%, 70%, 70%, and 80% during the intervention phase, subsequently remaining at 65% and 70% in phase A2. Furthermore, observations revealed improvements in participation, attention, confidence in expressing opinions, and the ability to comprehend reading content. These findings demonstrate that using reading texts based on the Maternal Reflective Method effectively enhances the reading comprehension skills of students with hearing impairments and serves as a suitable alternative instructional approach to support literacy development in both inclusive primary schools and special schools.